PENERAPAN GREEN INDUSTRY DAN GREEN HUMAN RESOURCE MANAGEMENT TERHADAP KINERJA KARYAWAN - Afriyeni, Afriyeni; Tiarawati, Tiarawati (Creative Research Management Journal, 2024)
Green Industry and Green Human Resource Management are one of the sustainability methods implemented by a company. This research aims to analyze the extent to which the implementation of Green Industry and Green Human Resource Management can improve employee performance, both from the aspects of productivity and environmental sustainability. This type of research is quantitative. The population of this study was all employees of the HR & General Department at PT Semen Padang, totaling 38 people taken by total sampling. Data were processed using multiple linear regression using a questionnaire. The research results show that there is an influence between green industry (X1) on employee performance, there is an influence of green human resource management (X2) on employee performance and there is a relationship between green industry and green human resource management on the performance of PT Semen Padang employees.